Prevalensi gangguan gastrointestinal pada anak autism spectrum disorder (ASD) di Pusat Layanan Autis Kota Denpasar tahun 2017 - Siswandewi, A.A. Istri Agung; Kamiati, Luh; Silakarma, Dedi (E-Jurnal Medika Udayana, 2018)
Gastrointestinal (GI) disorder is a medical condition which commonly complained by parents due to their effects on their autistic children which leads to behaviour disorder and medical problem amongst their children. Difficulty in detecting medical condition among ASD children is due to the communication barrier between parents and children which induced by the difficulty of their children to demonstrate their expression to their parents. As a result, the potential for GI disorders is not regularly detected in ASD children. This study was conducted to determine the prevalence of GI disorders amongst ASD children by sex and age group in Denpasar Centre for Autism in 2017. This cross-sectional study was conducted by total sampling method with 56 samples. Primary data which were used in this study was collected by handing questionnaire to the parents of ASD children. Results showed that the highest prevalence of GI disorders were constipation 35.7% followed by abdominal pain over 12.5%, flatulence 10.7%, and diarrhoea 7.1%. Meanwhile, the least prevalence was lower abdominal pain with the rate 3.6%. Males with ASD are more likely to present GI disorders rather than female. Furthermore, the highest prevalence of GI disorders was in the age group of 6-10 years. This study revealed that the prevalence of GI disorders amongst ASD children was slightly high. However, further research is required with wider range of sample to investigate this issue. Keywords: ASD, GI disorder, Prevalence